RELATIONS OF IMPROVEMENT OF DRUG USERS AND THE AVAILABILITY OF MEDICAL PERSONS WITH HIV / AIDS IN Correctional Institutions - Butar Butar, Herry Fernandes; Hamzah, Imaduddin (Polteknik Ilmu Pemasyarakatan, 2019)
The change of health paradigm on the world causing policy’s transformation and public concern regarding enhancement on Indonesian health rate rating. Medical problem happens in every line of social life, especially at Correctional Institutions and Correctional Detention Center as the place for criminals. Narcotics as one of the biggest problems in Correctional Sub-organizations are still one of the biggest contributors on overcrowded prison situations. This research intends to describe correlation between drug users and prisoners with HIV in prison. Methods being used are statistic correlative with qualitative approach which data obtained from Correctional Database System. Those data are narcotics users and prisoners with HIV in Correctional Suborganizations at 33 Ministry of Law and Human Rights Region Office. It can be concluded that the correlation between two variables is moderate relation.